2023
DOI: 10.3390/jcdd10070271
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Diversity of Visceral, Subcutaneous and Perivascular Adipose Tissue in a Vascular Surgery Population

Abstract: The prevalence of obesity has doubled, with a concomitant increase in cardiovascular disease. This study aimed to compare the characteristics of visceral, subcutaneous and peri-aortic adipose tissue determined with computed tomography (CT) scans and to correlate them with cardiovascular risk factors, anthropometric measures and medication. An observational and prospective study was conducted, and 177 subjects were included. Peri-aortic adipose tissue had the highest density, while the subcutaneous adipose tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Analysing the anthropometric measures, we found that patients with PAD had a lower HC when compared to those with varicose veins. Our multiple linear regression analysis showed that both smoking load and the presence of PAD were associated with a lower HC, which is the best anthropometric measure to determine SAT [15].…”
Section: Anthropometric Measures Pad and Lecvdmentioning
confidence: 74%
See 3 more Smart Citations
“…Analysing the anthropometric measures, we found that patients with PAD had a lower HC when compared to those with varicose veins. Our multiple linear regression analysis showed that both smoking load and the presence of PAD were associated with a lower HC, which is the best anthropometric measure to determine SAT [15].…”
Section: Anthropometric Measures Pad and Lecvdmentioning
confidence: 74%
“…A previous publication from our research team found that smoking load was negatively correlated with the area of SAT determined on CT scan in a cohort of vascular surgery patients, and these results could be explained by the inhibition of lipogenesis caused by nicotine inhalation [15,16].…”
Section: Anthropometric Measures Pad and Lecvdmentioning
confidence: 96%
See 2 more Smart Citations